Влияние некоторых заболеваний карпа на гематологические показатели - Головина, Н.А.; Поддубная, А.В.; Манкирова, В.Б. (Вестник зоологии, 1977)
The picture of carp blood with diseases of infectious, mycosic and invasion origin was studied. Each disease evokes definite essential deviations in the carp organism which may be used as one of characters for diagnosis of these diseases.